Unraveling the impact of nitric oxide, almitrine, and their combination in COVID-19 (at the edge of sepsis) patients: a systematic review - Wang, Ying; Yu, Qian; Tian, Yuan; Ren, Shiying; Liu, Liping; Wei, Chaojie; Liu, Renli; Wang, Jing; Li, Dong; Zhu, Kun (Frontiers in Pharmacology, 2024)
During the coronavirus disease 2019(COVID-19) pandemic, a large many critically ill and severe COVID-19 patients meet the diagnostic criteria for sepsis and even septic shock. The treatments for COVID-19 patients with sepsis are still very limited. For sepsis, improving ventilation is one of the main treatments. Nitric oxide(NO) and almitrine have been reported to improve oxygenation in patients with 'classical' sepsis. Here, we conducted a systematic review and metaanalysis to evaluate the efficacy and safety of NO, almitrine, and the combination of both for COVID-19(at the edge of sepsis) patients. Method: A systematic search was performed on Embase, Pubmed, Cochrane Library, Web of Science, Wanfang Database, and China National Knowledge Infrastructure. Randomized clinical trials, cohort studies, cross-sectional studies, case-control studies, case series, and case reports in COVID-19 patients with suspected or confirmed sepsis. Study This is a provisional file, not the final typeset article characteristics, patient demographics, interventions, and outcomes were extracted from eligible articles. Results: 35 studies representing1,701 patients met eligibility criteria. Inhaled NO did not affect the mortality(OR 0.96,95%CI 0.33-2.8, I 2 =81%, very low certainty), hospital length of stay(SMD 0.62, 95%CI 0.04-1.17, I 2 =83%, very low certainty) and intubation needs(OR 0.82, 95%CI 0.34-1.93, I 2 =56%, very low certainty) of patients with COVID-19(at the edge of sepsis). Meanwhile, almitrine did not affect the mortality(OR 0.44, 95%CI 0.17-1.13, low certainty), hospital length of stay(SMD 0.00, 95%CI -0.29-0.29, low certainty), intubation needs(OR 0.94, 95%CI 0.5-1.79, low certainty) and SAEs(OR 1.16, 95%CI 0.63-2.15, low certainty). Compared with preadministration, the PaO2/FiO2 of patients with NO(SMD-0.87, 95%CI -1.08--0.66,I 2 =0%, very low certainty), almitrine(SMD-0.73,95%CI-1.06--0.4,I 2 =1%, very low certainty) and the combination of both(SMD-0.94, 95%CI-1.71--0.16,I 2 =47%, very low certainty) increased significantly. Conclusions: Inhaled NO, almitrine and the combination of the two drugs improved oxygenation significantly, but did not affect the patients' mortality, hospitalization duration and intubation needs. Almitrine did not significantly increase the patients' SAEs. Well-designed high-quality studies are needed for establishing a stronger quality of evidence.